UPAYA MENINGKATKAN KEMAMPUAN PENALARAN MATEMATKA SISWA MELALUIMODEL PEMBELAJARAN GROUPINVESTIGATION PADA MATERI BILANGAN BULAT - Adha Yunita Simanullang; Edy Surya (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2013)
This study aimed to know how to increase students’ ability to apply mathematical reasioning cooperative learning model Group investigation on the subject of integers in class VII SMP Negeri 17 Medan. This type of research is a classroom action research (classroom action research). Subjects in this study were students of class VII-s SMP Negeri 17 Medan as many as 32 students. The object of this research is  the improvement of students’ mathematical reasoning ability by applying the learning model of Group Investigation on material integers in class VII-2 SMP Negeri 17 Medan academic year 2014/2015. From the observations, the researchers found that the average value of observations increases from the first cycle to the second cycle. The results of observations of teachers increased from 2.78 in the good category in the first cycle to 3.3 with excellent category on the second cycle. So also with the observation of students increased from 2.68 in both categories in the first cycle to 3.27 in both categories in the second cycle. Of action I through the prevision of mathematical reasioning ability test I obtained 17 students (53.125 %) of 32 students have achieved mastery learning (value of 2.66). after the second act through the prevision of mathematical reasioning test II acquired 28 students (87.66 %) of the 32 students who have achieved mastery learning (2.66). An increse in the precentage of completeness in complaint